The Occurence of Colistin-Resistant Hypervirulent Klebsiellapneumoniae in China - Lu, Yang; Feng, Yu; McNally, Alan; Zong, Zhiyong (Frontiers in Microbiology, 2018)
Hypervirulent Klebsiella pneumoniae strains are usually susceptible to many antimicrobial agents including colistin. Here we report the isolation and characterization of several colistin-resistant hypervirulent K. pneumoniae clinical strains. K. pneumoniae strains recovered from blood samples were collected at a university hospital in China. MICs of colistin were determined using microdilution. Colistin-resistant strains were subjected to whole genome sequencing to reveal their clonal background, antimicrobial resistance determinants and virulence factors. Virulence assays were performed with strains carrying the mucoid phenotype regulator gene rmpA using wax moth larvae. The pmrB gene encoding a P344L substitution was cloned into a colistin-susceptible K. pneumoniae strain to examine whether the substitution confers colistin resistance. Five colistin-resistant hypervirulent K. pneumoniae were recovered from blood samples of patients in China, belonging to four sequence/capsular types (ST23:K1, ST412:K57, ST660:K16, ST700:K1) and carried the virulence factor rmpA. Three strains had the known colistin-resistant D150G substitution in PhoQ including one ST700:K1 strain also carrying mcr-1. The remaining two isolates had a P344L substitution of PmrB but cloning of pmrB encoding the substitution into a colistin-susceptible isolate did not alter MICs of colistin, suggesting that such a substitution did not confer resistance to colistin. In conclusion, the convergence of colistin resistance and hypervirulence in K. pneumoniae of multiple clonal backgrounds has emerged and may warrant further surveillance.